Gambaran Tingkat Pengetahuan Menyikat Gigi Dan Status Ohi-S Pada Siswa Kelas V SDN 1 Panjangrejo Bantul - Asri Khamdani; Suharyono Suharyono; Siti Hidayati (Poltekkes Kemenkes Yogyakarta, 2017)
Maintaining dental and oral health is one of the efforts to improve health. One of the causes of why a person neglects dental and oral health is poor knowledge of dental and oral hygiene. In addition to caries, oral hygiene is one of the important issues concerning oral cavities that require attention. Primary school-aged children need more attention because they are vulnerable to dental and oral health problems. The aims of this research were to investigate the level of tooth brushing knowledge and OHI-S in fifth-grade students of SD N 1 Panjangrejo, Bantul. It belongs to descriptive research. The results indicated that 74.4% of students had moderate knowledge of tooth brushing, 17.9% had poor knowledge and 7.7% of students had good knowledge. The results of OHI-S status were 69.2% of students had good OHI-S status and 30.8% had moderate OHI-S status. It can be concluded that the level of knowledge of tooth brushing in fifth-grade students of SD N 1 Panjangrejo Bantul was moderate criteria by 74.4% and the status OHI-S of students was good criteria by 69.2%. Most of them had moderate knowledge of tooth brushing and good status of OHI-S by 51.2%.